Trajetórias do Trabalho de Pedagogo Técnico Administrativo na Educação Superior da Universidade Federal de Uberlândia-UFU (1995-2020) - Rocha, Vânia Amaral da (2023)
This thesis is part of the Graduate Program in Education of the Faculty of Education of the Federal University of Uberlândia (PPGED/Faced/UFU) and associated to the line of research Trabalho, Sociedade e Educação – TSE. The problem discussed here arose from the following questions: why do we have a small number of technical-administrative pedagogues in Higher Education at UFU? Why is much of the academic community unaware of the existence of the position in question and the work that this professional develops in the institution? Based on these initial questions and their consequences, the professional experiences lived by pedagogues and pedagogues and perceived by managers of the university were investigated, proposing the following objectives: to recompose, through empirical research, the historical process of the social conditions in which the pedagogue constituted himself as a worker in Higher Education at UFU; to understand what the pedagogue's work is at the university, why and how he/she performs it; in addition to the meaning of this work in the perception of managers. The methodological approach used was qualitative, carried out by techniques from Oral History, which allows us to enter the social process of the object of study based on the testimonies of the participating subjects. Thus, it was possible to interpret knowledge and experiences that constitute different perceptions, reframing each trajectory through the narratives coming from the pedagogues and pedagogues who work at this university. The theme is anchored in the ideas of basic theorists such as Marx; Marx and Engels; Mészarós; Oliveira; Saviani; Thompson; and also in contemporary authors, fundamental to understand the object of research. For the analysis of the narratives, an interpretive-comprehensive reading was made. Eleven people were interviewed, four pedagogues (three men and one woman) and seven managers (two men and five women) from UFU. The experiences narrated validated the relevance of the research and motivated the study. From the analysis of these narratives, it was understood that the constitution of the trajectories in question requires, yes, the resignification defended in this thesis. The voices that echoed, originating from the professionals interviewed, allowed us to know and understand the concerns of these administrative technicians, who showed frustration for not developing the specific activities attributed to their position. Thus, it was possible to unveil a broad and complex part of the web of knowledge and practices of training in Pedagogy that is not effective in professional practice in this institution. In the end, with substantial evidence, proposals were made in order to respond with alternatives and possibilities capable of generating improvements in the work of UFU's administrative technicians, which also directly influences the quality of teaching at this university.